Penerapan Metode Computer Assisted Instruction (CAI) Pada Media Pembelajaran Interaktif Fashion Drawing dengan pada Kelas X Kompetensi Keahlian Busana Butik SMK NU 01 Kendal - Prihatmoko, Setiyo; Sumaryanto, Sumaryanto; Anja Robbi Dini (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Based on research conducted in SMK NU 01 Kendal, especially in fashion drawing learning in class X busana butik still uses conventional learning with blackboard media, the learning media is less effective because it requires a lot of energy and time for learning material that contains many pictures and tutorials that need to be delivered repeatedly. This study found a solution that is the design of learning media using the Computer Assisted Instruction (CAI) method, a system for delivering interactive multimedia-based learning with instructional material presented by means of a computer or computer system., so that it can help teachers deliver material effectively, and make students learn with high motivation because they are interested in multimedia systems that are able to present the appearance of text, images, videos, sounds and animations. The validation value by media experts shows that the value of 3.1 is classified as good / valid, and the validation results from material experts show a value of 3.5 which is categorized as very good / very valid, and an increase in the percentage value of effectiveness from 50.4% to 81.7%. and there is time efficiency, one of material such as collar images can save up to 18 minutes.